A hybrid derivation method for the conceptual analysis of legal knowledge bases - Paliulionienė, Laima (Lietuvos matematikos rinkinys, 1997)
In knowledge-based legislative engineering, the conceptual analysis of legal knowledge bases is to be used to compare and detect differences of variants of the legal document being prepared. as well as in other cases (to integrate parts of a legal document, to analyse the compatibility of two legal documents, etc.). In project NEMESIS, variants of a legal document are formalised and stored in knowledge bases. The knowledge representation formalism is based on F-logic. compare the variants, we propose a hybrid derivation method, which integrates formal derivation with difference analysis procedures.There are two stages of the use of the method: (1) the analysis of facts, when concepts and their instances are compared, (2) the analysis of rules, when consequences of rules are analysed. During one iteration of the analysis of rules, premises of a rule are used to made a test situation (a set of facts), then consequences of the situation are derived by bottom-up theorem proving based on model generation, and the consequences are analysed as facts at the first stage. In this way all rules, that are not common for the variants, are processed.